2008
DOI: 10.1016/j.jacc.2007.09.071
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Change in Plaque Size, Composition, and Molecular Footprint After Recombinant Apolipoprotein A-IMilano (ETC-216) Administration

Abstract: Acute plaque regression observed after short-term apoA-I(Milano) administration was associated with a significant reduction in suspected makers of plaque vulnerability in an experimental model of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 24 publications
5
73
0
1
Order By: Relevance
“…10,11 Animal studies have shown that increases in HDL acutely change plaque composition. [12][13][14] Although there have been studies showing that plaque characteristics, as assessed with IVUS, change in the coronary circulation after HDL infusions, histological changes have not been studied. The primary goal of this study was to determine the effects of reconstituted HDL (rHDL) on serum markers of inflammation and on atherosclerotic plaque composition.…”
mentioning
confidence: 99%
“…10,11 Animal studies have shown that increases in HDL acutely change plaque composition. [12][13][14] Although there have been studies showing that plaque characteristics, as assessed with IVUS, change in the coronary circulation after HDL infusions, histological changes have not been studied. The primary goal of this study was to determine the effects of reconstituted HDL (rHDL) on serum markers of inflammation and on atherosclerotic plaque composition.…”
mentioning
confidence: 99%
“…Despite a lipid profile that is usually associated with a high risk of premature cardiovascular disease, apoA-I M carriers display no increase in cardiovascular disease or events (10,14,15). This has led to speculation that apoA-I M is a gainof-function mutation that has enhanced cardio-protective effects (16)(17)(18)(19)(20)(21)(22), while others believe that wild-type (WT) apoA-I and apoA-I M are functionally equivalent (23,24). A clinical trial of repeated intravenous infusions of apoA-I M -phospholipid complexes demonstrated regression of existing atheromas after five weekly treatments (25,26).…”
mentioning
confidence: 99%
“…It offered the opportunity to assess the short-and long-term effects of repeat administrations of MDCO-216 on plasma lipid and lipoprotein levels, and the effect of treatment on the exvivo serum cholesterol effl ux capacity via currently known effl ux mechanisms. The opportunity had additional relevance since little information has been published on the effects of exogenous apoA-1M administration on lipids and lipoproteins in animals fed a normal diet; previous animal studies were focused on the effect of apoA-IM administration on lipid levels and atherosclerosis in cholesterol-fed animals (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, administration of the predecessor compound ETC-216 was shown to reduce atherosclerotic plaque size and volume in mice and rabbit models (16)(17)(18)(19)(20) and in patients with acute coronary syndromes ( 21 ). However, no studies have been reported describing the effects of repeated administration of this product candidate on lipid and lipoprotein levels, either in animals or in man.…”
Section: Methodsmentioning
confidence: 99%